Al-Quran dan Budaya: Al-Quran dalam Siklus Kehidupan Muslim - Ali Ridho (Fakultas Ushuluddin Adab dan Humaniora (FUAH), Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2019)
The purpose of this paper is to find out the relationship between the Qur'an and Culture and how to become a good Muslim based on the values ​​of the Qur'an and Culture. The research method used is qualitative in the form of library studies. Data is collected by researching books and journals and other sources that support research activities. The results of this study are that Islam is not born of cultural products. However, it builds a culture, a civilization. A civilization based on the Qur'an and the Sunnah of the Prophet. that is finally called Islamic civilization. With this, we can begin to put Islam in our daily lives. Building Islamic culture with a foundation of concepts derived from Islam with its source is the Qur'an. The life of a Muslim must be following the rules set by the Qur'an. Muslims must be able and reluctant (upholding) to uphold a culture that is a local identity in themselves with the foundation of the holy values ​​contained in the Qur'an. Among them is a sincere, knowledgeable and honest attitude to be a Muslim person in undergoing a time struggle that continues to change along with changing patterns of human civilization. Thus, there is no reason for a Muslim to lose his cultural identity to become a good Muslim. Because Al-Qur'an and Culture are clothes that are suitable to be worn by every Muslim in every fragment of life rites